Reference performance values of pre-seasonal physical fitness in elite youth male football players in Greece. - Smpokos, Emmanouil; Mourikis, Christos; Tsikakis, Antonios; Katsikostas, Nikolaos; Linardakis, Manolis (Journal of Public Health: From Theory to Practice (2198-1833), 2022)
Purpose: Current study aimed to establish percentile normative data and to find age differences in fitness performance tests of 14–19-year-old footballers played in a Greek elite youth football academy. Methods: A total of 216 male players from four different chronological age groups of the same club, from under 15 to under 19 (U-15, U16, U17 & U-19) for 5 consecutive years (2014–2018) who played in six different positions — as midfielders, defenders, wingbacks, wingers, forwards, and goalkeepers — participated in the study, with 426 measurements. Measured variables of weight, height, body mass index (BMI), squat jump (SJ), countermovement jump test (CMJ), countermovement jump test with arm swing (CMJAS) isokinetic strength peak torque (PT) ratio of hamstring (H) and quadriceps (Q) at speed of 60°·s, sit & reach test (i.e., flexibility), aerobic maximal exercise test on a treadmill to exhaustion (VOmax), and velocity at VOmax were recorded and compared among age groups during the period 2014–2018. Age and performance physical fitness parameters values (i.e., P to P) were generated using Box–Cox power transformations. Results: The elite footballers had mean age of 15.6 ± 1.4 years, body weight 66.7 ± 7.8 kg, height 1.757 ± 0.064 cm and BMI 21.6 ± 1.7 kg·m. Performance across all testing variables was increased according to age, with each age scoring higher/better than their younger counterparts from the U-15 squad up. Velocity at lactate threshold (VL-Km/h) was 13.6, 13.4, 13.1, and 13.2 Km/h, for the four age groups respectively, and 203.5, 201.9, 187.8, and 177.4 Nm in extension of left quadriceps in 60°·s peak torque, Q (Nm). Moreover, the U-19 presented superior performance in VOmax (Vvomax) to the other age categories (18.2, 17.9, 17.4, and 17.3 km/h, respectively). Footballers' flexibility and jump ability were more developed in U-19 age group compared with other group ages. Conclusion: Findings indicated that U-19 players performed better than younger players in all assessments. This may have been possible due to the differences in training experience, and individual levels of strength/power/endurance ability. Moreover, establishing normative performance values will allow practitioners to more accurately identify deficiencies in performance that are relative to their athletes.